2016
DOI: 10.1186/s12986-016-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with the MC4R rs17782313 variant, mental stress and energy intake and the risk of obesity in Genome Epidemiology Study

Abstract: BackgroundThe melanocortin-4 receptor (MC4R) regulates metabolism by modulating eating behavior and MC4R variants (rs17782313 and rs571312) are associated with obesity in Asians and Caucasians. However, the impact of their interactions with nutritional and lifestyle factors on obesity are poorly described. Therefore, we investigated the interaction of MC4R variants and dietary patterns on the risk of obesity in Korean middle-aged adults.MethodsData collected included, genetic variations, anthropometric and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 45 publications
(82 reference statements)
0
50
1
Order By: Relevance
“…Interactions between genetic and environmental factors play an important part in the etiology of MS and obesity 21. MS diagnosed on the basis of the IDF criteria of 2005 was observed in 39.3% of women with the T/T genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between genetic and environmental factors play an important part in the etiology of MS and obesity 21. MS diagnosed on the basis of the IDF criteria of 2005 was observed in 39.3% of women with the T/T genotype.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported further by our finding that rs6567160 near the MC4R gene was the main variant driving the interaction with depression on BMI. Interestingly rs17782313, which is in perfect LD with rs6567160, has previously been reported to interact with stress, and influence obesity risk (Park et al, ). The importance of the MCR4 gene in the depression‐high BMI relationship is also evident in animal‐based pharmacological studies, in which the antagonist of MCR4 receptor has shown anxiolytic and antidepressant effects, particularly under conditions of high stress (Okubo & Chaki, ).…”
Section: Discussionmentioning
confidence: 99%
“…Information on age, education, income, smoking history, alcohol consumption, and physical activity was collected during a health interview, and physical characteristics such as height, weight, and body composition were measured as described in the previous studies [20,21]. The stress level was evaluated by asking subjects to answer 10 questions concerning their state of agitation and anxiety in the workplace and family situations in their daily life.…”
Section: Baseline Characteristics Of Subjects Of the Kare Studymentioning
confidence: 99%
“…DNA samples from the participants were isolated from their peripheral blood, and genotyping was conducted using the Affymetrix Genome-Wide Human SNP array 5.0 (Affymetrix, Santa Clara, CA, USA). The accuracy of the genotyping was checked using the Bayesian Robust Linear Modeling with the Mahalanobis Distance genotyping algorithm [21]. The exclusion criteria of genotyping were as follows: low genotyping accuracies (< 98%), high missing genotype call rates (≥4%), high heterozygosity (> 30%), and gender bias.…”
Section: Genotyping and Quality Control Of The Pcos And Kare Studiesmentioning
confidence: 99%
See 1 more Smart Citation